Daily intake of phthalates, MEHP, and DINCH by ingestion and inhalation. (October 2018) - Weiss, Jana M.; Gustafsson, Åsa; Gerde, Per; Bergman, Åke; Lindh, Christian H.; Krais, Annette M.
Abstract: Phthalate esters, suspected endocrine disrupting chemicals, are used in a wide range of applications. Because phthalate esters are not covalently bound, they can easily leach into the indoor environment and associate to dust particles. Thus, exposure may occur through inhalation, ingestion, or contact with the skin. However, it is unclear to what degree indoor dust contributes to the daily intake of phthalate esters. This study investigates household dust as an exposure pathway for seven phthalate esters, the monoester MEHP, and the plasticizer DINCH. Household dust collected from children's sleeping rooms and from living rooms were analysed using gas and liquid chromatography tandem mass spectrometry. To compare two exposure pathways, different dust particle sizes were generated: a respirable fraction (<5 μm) and an ingested particle fraction in the anticipated size range of skin adherence (<75 μm). Modelling of dust inhalation and ingestion showed that the daily intake of dust-bound phthalate esters was likely to be 2 times (inhalation) to 12 times (ingestion) higher for 21-month-old children than for adults. These children's daily uptake of phthalate esters was 40–140 times higher through ingestion than inhalation. Furthermore, dust may be an exposure pathway for phthalate esters as well as for MEHP. Therefore, phthalate monoesters could be environmental contaminants of their own and need to be considered in health risk assessments. Highlights: Five phthalate esters and one monoester (MEHP) could be quantified in all dust samples. The EDI of DEHP and MEHP via ingestion of dust for a 21-month old is 727 and 277 ng/kg bw respectively. Our modelling data suggest that inhalation is a minor pathway of exposure compared to ingestion. The EDI of phthalate esters for adults are 2–12 times lower than for 21-months old. Dust is a direct exposure pathway for the transformation product MEHP and should be considered in health risk assessments.